Medial Migration of a Broken Trochanteric Cable - Bedri Karaismailoglu; Turgut Nedim Karaismailoglu (Case Reports in Orthopedics)
Background. Cerclage wires or cables are commonly being used in hip reconstruction procedures like primary (especially in patients with developmental hip dysplasia) or revision arthroplasty. Local or distant migration of a broken cable or wire is a complication that might lead to devastating situations depending on the route of migration. Case Presentation. We report a case of a 40-year-old female who underwent bilateral total hip arthroplasty surgery due to bilateral developmental hip dysplasia. Trochanteric osteotomy was needed in her right hip to advance trochanter major distally. Trochanteric fixation was achieved by a cerclage cable system. Four years after the surgery, the patient referred to the hospital with a prominence and pain in her right inguinal area. Radiographies revealed medial migration of a broken trochanteric cable part. The possible route of the cable was through medial adductor muscles, posterior to the femoral neurovascular bundle and anterior to the sciatic nerve. Both migrated and remaining parts of the cable were extracted under general anesthesia. Conclusion. Broken cables should be followed carefully due to their sharpness and possible serious complications secondary to distant migration. Extraction might be inevitable in case of a close relation with neurovascular structures.